Effect of TNF and LTA polymorphisms on biological markers of response to oxidative stimuli in coal miners: a model of gene-environment interaction. Issue 2 (1st February 2003) - Nadif, R; Jedlicka, A; Mintz, M; Bertrand, J-P; Kleeberger, S; Kauffmann, F
Abstract : Introduction: Interaction between genetic background and oxidative environmental stimuli in the pathogenesis of human lung disease has been largely unexplored. Methods: A prospective epidemiological study was undertaken in 253 coal miners. Intermediate quantitative phenotypes of response to oxidant exposure, including erythrocyte glutathione peroxidase (GSH-Px) and catalase activities, were studied. Oxidant exposures studied were smoking habits and cumulative dust exposure assessed by job history and ambient measures. Disease phenotypes included subclinical computed tomography score at the first survey and x ray profusion grades twice, five years apart, to assess established coal workers' pneumoconiosis (CWP). Miners were genotyped for common functional polymorphisms in the gene for tumour necrosis factor α ( TNF ) and lymphotoxin α ( LTA ), two proinflammatory cytokines that have been implicated in the pathogenesis of chronic lung diseases. Results: Regarding gene-environment interaction on intermediate phenotypes, results showed interaction of a promoter polymorphism at the –308 position in TNF with occupational exposure on erythrocyte GSH-Px activity with a significant association in those with high exposure (p=0.003), whereas no association was observed among those with low exposure (interaction p=0.06). Regarding gene intermediate phenotype interaction on clinical outcome, results showed an association of CWP prevalence with an Nco I polymorphism in LTA in those with low catalase activity (p=0.05), whereas no association was observed in those with high activity (interaction p=0.03). No other significant association was observed. Conclusion: The results suggest that interactions of genetic background with environmental exposure and intermediate response phenotypes are important components in the pathogenesis of CWP.